QRDR変異を有する肺炎球菌に対するラスクフロキサシンのインビトロ活性の評価 - 村田, 美香 (American Society for Microbiology, 2019)
Nagasaki University (長崎大学) 博士(医学) Lascufloxacin showed potent activity against Streptococcus pneumoniae with a GyrA or ParC mutation (first-step mutant). The frequency of selecting resistant strains tended to be lower for lascufloxacin than for levofloxacin and garenoxacin after drug exposure in first-step mutants but was similar in the comparison between lascufloxacin and moxifloxacin. The increase in MIC was smaller for lascufloxacin than for levofloxacin, garenoxacin, and moxifloxacin when clinical strains with only ParC mutations were exposed to the corresponding drug. 長崎大学学位論文 学位記番号:博(医歯薬)甲第1138号 学位授与年月日:平成31年3月20日 Author: Mika Murata, Kosuke Kosai, Shunsuke Yamauchi, Daisuke Sasaki, Norihito Kaku, Naoki Uno, Yoshitomo Morinaga, Hiroo Hasegawa, Taiga Miyazaki, Koichi Izumikawa, Hiroshi Mukae, Katsunori Yanagihara Citation: Antimicrobial Agents and Chemotherapy, 62(4), e01971-17; 2018 Nagasaki University (長崎大学), 博士(医学) (2019-03-20) doctoral thesis